Numerical simulation and experimental validation of large pressure pulsation in reciprocating compressor. (February 2019) - Li, Yuan; Quan, Kai; Wu, Rui; Chang, Yunfeng; Guo, Bei; Zhang, Bo
Abstract: A numerical model based on the one-dimensional unsteady flow theory was established to simulate the large pulsation of the reciprocating compressor. The simulation model was consisting of the single straight pipeline system, the straight pipe +volume chamber pipeline system and the straight pipe + reducer pipeline system. The models were solved by using the two steps method and the method of characteristics. To validate the simulation model, the experiment to measure the pressure pulsation was done in different exhaust pressures, different rotate speeds and different pipeline systems. The waveforms of the simulation results and the experimental results were in good agreement and all of the relative errors of the pressure unevenness were below 10%. The simulation results were consistent with the experiment results. The model established in this paper was accurate.